Premenstrual syndrome and premenstrual dysphoric disorders among Jordanian women. Issue 3 (7th December 2017) - Albsoul‐Younes, Abla; Alefishat, Eman; Farha, Rana Abu; Tashman, Lina; Hijjih, Enas; AlKhatib, Rasha
Abstract: Purpose: The aim of this study was to investigate the frequency, associated factors, and management approaches of premenstrual dysphoric disorder (PMDD) and premenstrual syndrome (PMS) in Jordanian women. Design and Methods: Three hundred premenopausal women completed a self‐administered questionnaire. Findings: Moderate–severe PMS was reported by 29% of women, while 14% had PMDD. Younger unmarried women had the more severe condition. Herbal remedies and no medication were the most common approaches used to manage PMS/PMDD. Implications for Nursing Practice: High rates of PMS and PMDD found in this study highlight the need to increase awareness to this condition among health providers in order to facilitate its identification, diagnosis, and management.